Предмет:
МатематикаАвтор:
аноним((a + b)^2 - (a - b)^2) * (1 / a + 1 / b) = ((a + b) + (a - b) * (a + b) - (a - b)) * (1 / a + 1 / b) = (a + b + a - b) * (a + b - a + b) * (1 / a + 1 / b) = 2a * 2b * (1 / a + 1 / b) = 4ab * ((b + a) / ab) = 4ab * (a + b) / ab = 4(a + b).
Найдём числовое значение этого выражения при
a = 1 - √7; b = 3 + √7:
4(a + b) = 4 * (1 - √7 + 3 + √7) = 4 * 4 = 16.
Ответ: 16.
Автор:
maximus92Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть